2019
DOI: 10.1080/23746149.2019.1662733
|View full text |Cite
|
Sign up to set email alerts
|

Optical spatial shock waves in nonlocal nonlinear media

Abstract: Dispersive shock waves are fascinating phenomena occurring when nonlinearity overwhelms linear effects, such as dispersion and diffraction. Many features of shock waves are still under investigation, as the interplay with noninstantaneity in temporal pulses transmission and nonlocality in spatial beams propagation.Despite the rich and vast literature on nonlinear waves in optical Kerr media, spatial dispersive shock waves in nonlocal materials deserve further attention for their unconventional properties. Inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 108 publications
1
15
0
Order By: Relevance
“…hypertonic > isotonic > hypotonic) was confirmed from direct measurements by optical tweezers experiments. Interestingly, we also found that in aged blood samples, which feature high free Hb content, the nonlinear beam dynamics is dramatically different (Figure 5(c)): at a higher concentration of Hb, a stronger self-focusing nonlinearity was observed first, and then thermal defocusing took over leading to shock-wave like patterns [22,66]. The underlying mechanism for optical nonlinearity-induced wave dynamics in such biological media certainly merits further studies.…”
Section: Nonlinear Self-guiding Of Light In Living Biological Suspensionsmentioning
confidence: 81%
“…hypertonic > isotonic > hypotonic) was confirmed from direct measurements by optical tweezers experiments. Interestingly, we also found that in aged blood samples, which feature high free Hb content, the nonlinear beam dynamics is dramatically different (Figure 5(c)): at a higher concentration of Hb, a stronger self-focusing nonlinearity was observed first, and then thermal defocusing took over leading to shock-wave like patterns [22,66]. The underlying mechanism for optical nonlinearity-induced wave dynamics in such biological media certainly merits further studies.…”
Section: Nonlinear Self-guiding Of Light In Living Biological Suspensionsmentioning
confidence: 81%
“…A further possibility is to consider an array of optical lenses, which, as shown in [76], may also emulate a parabolic medium. A further possible framework is given by highly nonlocal nonlinear optical systems, as thermal media, where related studies have been reported [77,78].…”
Section: Precession In Analogs and Real Experiments With Quantum Fluidsmentioning
confidence: 99%
“…Simple Riemann waves (RWs) are implicit solutions of the inviscid Burgers' equation (IBE), that lies at the basis of fluid dynamics. These waves are of fundamental importance in studying shock wave phenomena occurring not only in hydrodynamics but also in numerous other physical systems [1][2][3][4][5][6][7][8][9][10][11][12]. Interest in RWs arises from the main role played by the IBE, a paradigm nonlinear partial differential equation which is used to model nonlinear and turbulent systems of various complexity, spanning dynamics encountered in e.g.…”
Section: Introductionmentioning
confidence: 99%